Combined Positive Score and Cisplatin Sensitivity Are Prognostic Factors for Response to Nivolumab Therapy for Recurrent Metastatic Squamous Cell Carcinoma of the Head and Neck - Hiroaki Iijima; Akihiro Sakai; Koji Ebisumoto; Go Ogura; Mayu Yamauchi; Takanobu Teramura; Aritomo Yamazaki; Takane Watanabe; Toshihide Inagi; Ryoko Yanagiya; Ai Yamamoto; Hiroshi Ashida; et al. (Clinical Medicine Insights: Oncology, 2024)
Background: Recurrent or metastatic squamous cell carcinoma of the head and neck (R/MHNSCC) is a challenging malignancy with a poor prognosis and limited treatment options. Nivolumab, an immune checkpoint inhibitor (ICI) targeting the programmed cell death/programmed cell death ligand 1 (PD-1/PD-L1) pathway, has emerged as a promising therapy for these patients. However, identifying biomarkers predictive of response to nivolumab remains critical for optimizing treatment strategies. Previous studies have suggested that PD-L1 expression, as determined by the Combined Positive Score (CPS) and other clinical factors, may influence treatment outcome. This study aims to retrospectively examine whether CPS can be a biomarker by staining PD-L1 with 22 C3 antibody in R/MHNSCC patients treated with nivolumab. Methods: This retrospective study reviewed the medical records of R/MHNSCC patients treated with ICIs at Tokai University Hospital from April 2017 to December 2022. We examined the relationship between response rate to ICI therapy, PD-L1 staining, biomarkers, and survival. Statistical analyses included t -test, chi-square test, and Cox regression. Results: This study included 92 nivolumab-treated patients. Combined Positive Score was evaluable in 53 of these patients. Patients with a CPS of 15 or higher had better progression-free survival (PFS) ( P  = .0171), with a median PFS) of 13 months. In the Various Definitions analysis, cisplatin-sensitive patients also had good PFS ( P  = .0295). The cisplatin-sensitive patient population with a CPS of 15 or higher had the best PFS, with a median of 14 months ( P  = .006). There was no significant difference in overall survival (OS) by CPS value. Immune-related adverse events did not affect OS or PFS. Conclusions: CPS ⩾ 15 and cisplatin sensitivity are promising prognostic markers for nivolumab therapy in R/MHNSCC. Considering these biomarkers in patient selection could maximize the therapeutic benefits of nivolumab. This finding may help to optimize ICI therapy strategies.